2011
DOI: 10.1186/1741-7007-9-15
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency and the sex chromosomes from yeasts to humans

Abstract: BackgroundHaploinsufficient (HI) genes are those for which a reduction in copy number in a diploid from two to one results in significantly reduced fitness. Haploinsufficiency is increasingly implicated in human disease, and so predicting this phenotype could provide insights into the genetic mechanisms behind many human diseases, including some cancers.ResultsIn the present work we show that orthologues of Saccharomyces cerevisiae HI genes are preferentially retained across the kingdom Fungi, and that the HI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Haplo-insufficient genes have been well characterized in Saccharomyces cerevisae and can be used to predict haplo-insufficiency in other metazoan species (de Clare et al 2011). Orthologs of yeast haplo-insufficient genes are excluded from the X chromosome in humans and C. elegans (de Clare et al 2011). Here, we found that this trend holds for the four other nematode species ( Figure 8B).…”
Section: Effect Of X Localization On Gene Expressionsupporting
confidence: 64%
See 1 more Smart Citation
“…Haplo-insufficient genes have been well characterized in Saccharomyces cerevisae and can be used to predict haplo-insufficiency in other metazoan species (de Clare et al 2011). Orthologs of yeast haplo-insufficient genes are excluded from the X chromosome in humans and C. elegans (de Clare et al 2011). Here, we found that this trend holds for the four other nematode species ( Figure 8B).…”
Section: Effect Of X Localization On Gene Expressionsupporting
confidence: 64%
“…A reduction in their gene copy number from two to one results in a significant reduction of overall fitness. Haplo-insufficient genes have been well characterized in Saccharomyces cerevisae and can be used to predict haplo-insufficiency in other metazoan species (de Clare et al 2011). Orthologs of yeast haplo-insufficient genes are excluded from the X chromosome in humans and C. elegans (de Clare et al 2011).…”
Section: Effect Of X Localization On Gene Expressionmentioning
confidence: 99%
“…Sex chromosomes are subject to unique evolutionary processes and mechanisms (5,(45)(46)(47). Our observations about the yeast MAT chromosome are reminiscent of the movement of genes out of the mammalian X chromosome (48,49), but unlike that process we do not suggest that the "out-of-MAT" gene movements are driven by natural selection.…”
Section: Discussionmentioning
confidence: 63%
“…However, their results are not comparable with ours because they examined yeast growth in a medium containing glucose (YPD) that represses RC genes, while we performed our experiments in YPG, which forces the cells to rely on mitochondrial respiration and therefore stimulates the expression of RC genes. Another study showed that in yeast haploinsufficient genes are overrepresented in chromosome III,14 but COQ4 maps to S cerevisiae chromosome IV.…”
Section: Discussionmentioning
confidence: 99%